Analisis Pengalaman Transformative Travel Wisatawan di Museum Topeng Kota Cirebon - Ety Setiawati; Widia Ningsi (Fakultas Teknik Universitas Cenderawasih, 2026)
Evolving tourism trends indicate a transition among tourists from merely visual recreation (hedonic) toward transformative travel (eudaimonic), which is oriented toward self-reflection and the search for meaning in life. Museum Topeng Cirebon holds significant potential for transformative tourism due to its mask collection that is rich in life philosophies. The urgency of this research is to analyze these transformative tourism experiences to support the quality of tourists' intellectual experiences and the sustainability of local culture. This qualitative research employed thematic analysis with purposive sampling techniques, involving 70 respondents who completed a Google Form questionnaire, which was further supported by interviews and a literature review. The results from the pre-visit phase showed that initial motivations were dominated by hedonic tourism at 37.1%. During the visit, a transformation occurred; tour guides acted as human catalysts in building narrative engagement (62.9%), and the chronological, philosophical flow of the masks sparked an awakening of consciousness for 80% of respondents. In the post-visit phase, eudaimonic impacts were experienced by 91.4% of respondents, including an expanded worldview (37.1%) and a commitment to becoming agents of cultural change (27.1%). However, operational challenges remain, including inconsistent opening hours and a lack of digital self-information facilities.